Method for constructing force-electricity performance prediction model of bicontinuous phase electrolyte
By preparing and characterizing bicontinuous phase solid electrolytes with different ratios, establishing a three-dimensional solid RVE model and performing simulation analysis, the problem of difficulty in predicting the change in force-electric coupling performance of bicontinuous phase solid electrolytes in the prior art is solved, and parameterized prediction and design optimization of their force-electric performance are achieved.
Patent Information
- Application Number
- CN202411641164.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art is difficult to accurately predict the change in force-electric coupling performance of bicontinuous phase solid electrolytes in multiphysics fields, and there is a lack of parameterized analysis and prediction performance methods.
By preparing bicontinuous phase solid electrolyte samples with different ratios, structural, mechanical and electrochemical properties are characterized, a three-dimensional solid RVE model is established, and mechanical and electrochemical performance parameters are obtained using simulation analysis methods. Then, Ashby's method was used to evaluate the multifunctional efficiency, fit the relationship between porosity, pore size and force-electric performance efficiency, and predict the force-electric performance change law under different ratios.
Parameterized prediction of the force-electric performance of bicontinuous phase solid electrolyte is achieved, providing a reference for design and performance optimization, and improving the accuracy of its performance research in multiphysics fields.
Smart Images

Figure CN119601142A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of solid electrolytes, and specifically relates to a method for constructing a prediction model for the mechanical-electrical properties of a dual-continuous-phase electrolyte. The model involved mainly predicts the mechanical properties, electrochemical properties, and mechanical-electrical coupling properties of dual-continuous-phase solid electrolytes with different geometric characteristics such as porosity and pore size. Background Art
[0002] With the continuous development of energy storage and conversion technology, solid electrolytes, as a new type of electrolyte material with high ion conductivity and excellent stability, have received much attention. Solid electrolytes, with their high safety and high energy density potential, are becoming a research hotspot in the field of new energy, especially polymer bicontinuous phase solid electrolytes, which are used in structure-energy storage integrated devices due to their superior multifunctional properties. However, the design and performance research of polymer bicontinuous phase solid electrolytes still face challenges, especially in terms of their multifunctional performance under multi-physical fields, which requires further research.
[0003] At present, the research on the related properties of dual-continuous-phase solid electrolytes is mainly experimental research, and no relevant parametric research has been conducted to provide a reference for the forward design and performance prediction of dual-continuous-phase solid electrolytes.
[0004] Polymer bicontinuous solid electrolyte is a composite material composed of polymer and ionic liquid, in which the polymer and ionic liquid form a bicontinuous phase structure, and the polymer provides a porous skeleton and transmission channel for the ionic liquid. This structure allows efficient ion conduction while maintaining mechanical stability and good interfacial compatibility. The mechanical properties of the polymer porous structure directly affect the transmission of ions and thus the electrochemical properties of the solid electrolyte. Especially when used in structure-energy storage integrated devices, the solid electrolyte will be subjected to the effect of external loads, and the study of the mechanical properties of the polymer porous skeleton is more important. The performance of the electrolyte part has also become a key factor restricting the multifunctional coupling and performance improvement of structure-energy storage integrated devices. With the development of computer simulation technology in recent years, relevant research can be accelerated based on computer simulation technology. The complex pore structure inside the porous skeleton of epoxy resin-based solid electrolyte polymers brings difficulties to the modeling and simulation analysis process.
[0005] Regarding the study of multi-physical field coupling performance of solid electrolytes and structural-energy storage integrated devices, Hedayati, D. Peyrow, et al. "Numerical Simulation of the One-Way Mechanical-Electrochemical Coupling in Structural Supercapacitors." modeled and numerically simulated mechanical-electrochemical coupling in dual-continuous phase solid electrolytes, and studied its effect on the performance of structural supercapacitors under compressive loads. However, in this study, only a two-dimensional model of the dual-continuous phase solid electrolyte was established and simulated, and the complex three-dimensional porous structure of the epoxy resin-based solid electrolyte could not be accurately expressed, especially when the liquid and solid phase volumes were relatively large. It cannot meet the needs of more in-depth simulation research on solid electrolyte performance and performance simulation of solid electrolytes under more raw material ratios, and the accuracy of the model and simulation method has not been verified by necessary experiments. Tu V, Asp LE,Shirshova N, et al. Performance of bicontinuous structural electrolytes[J].Multifunctional Materials, 2020, 3(2): 025001. In order to explore the microstructural properties with better multifunctional performance, a program was proposed to generate various categories of synthetic microstructures with a wide range of properties for computer simulation. The effective performance of the generated artificial structured electrolytes was obtained through virtual material testing and compared with the experimental data. The microstructural category with better multifunctional performance was determined, but its structural model was not used for more in-depth performance simulation verification and multi-physics field coupling performance research.
[0006] In summary, since bicontinuous-phase solid electrolytes have both carrying capacity and energy storage capacity, and their working conditions are under the joint influence of multiple physical fields, there are significant differences in the characteristics of traditional electrolytes, and there are also differences in the parametric research methods for their performance. In addition, the research on bicontinuous-phase solid electrolytes is just in its infancy, and there is a lack of methods for parametric analysis and performance prediction. Existing methods cannot accurately predict changes in the mechanical-electrical coupling properties of bicontinuous-phase electrolytes. Summary of the invention
[0007] In order to solve the above problems, the present invention proposes a method for constructing a prediction model of the mechanical and electrical properties of a dual-continuous phase electrolyte. The technical solution adopted is as follows:
[0008] A method for constructing a prediction model for the mechanical and electrical properties of a bicontinuous phase electrolyte, the specific steps of the method are as follows:
[0009] Step 1: Prepare several dual-continuous phase solid electrolyte samples with different ratios of epoxy resin components and ionic liquids;
[0010] Step 2: Perform structural characterization, mechanical property characterization and electrochemical property characterization on the dual-continuous phase solid electrolyte sample prepared in step 1;
[0011] Step 3: Establishment of three-dimensional solid RVE model and simulation analysis method of dual-continuous phase solid electrolyte
[0012] 1) First, set the size of the cube space, and calculate the number of spheres required for modeling in the cube space based on the maximum pore size, minimum pore size and porosity data obtained in step 2. The formula is as follows:
[0013]
[0014] In the formula, is the porosity; is the length of the cubic space region; is the width of the cubic space region; is the height of the cubic space area; is the maximum radius of the pore; is the minimum radius of the pores, and the coefficient 1.1 is used to compensate for the porosity error caused by factors such as pore overlap;
[0015] 2) The center position and radius of the sphere are randomly generated:
[0016] First, the center position of the sphere Using random uniform distribution, which ensures that the entire given space can be filled evenly, the constraints on the seed placement are set as , using a pseudo-random number generator to generate random position coordinates of the seed ,
[0017] Then, using a pseudo-random number generator, within the constraints of the sphere radius R , generate spherical seeds of random size;
[0018] 3) For each sphere, a 3D solid of the sphere was created by rotating the drawn 2D sketch in Abaqus software, and then Boolean operations were applied to subtract these spheres from the cubic matrix to create voids, thus obtaining a 3D solid RVE model of the dual-continuous phase solid electrolyte;
[0019] 4) Using the three-dimensional solid model of the EPE bicontinuous phase solid electrolyte with different porosities and pore sizes established in the above steps, the modulus of the bicontinuous phase solid electrolyte and the ionic conductivity of the bicontinuous phase solid electrolyte are obtained by simulation analysis;
[0020] Step 4: Establishment of a prediction model for the mechanical and electrical properties of a bicontinuous phase electrolyte:
[0021] 1) The method proposed by Ashby is used to evaluate the multifunctional efficiency, where the multifunctional efficiency ηMF is defined as the sum of the mechanical performance efficiency ηM and the electrochemical performance efficiency ηEC as shown in the following formula:
[0022]
[0023] Among them, the mechanical performance efficiency ηM is defined as the ratio of the modulus of the dual-continuous phase solid electrolyte to the modulus of pure epoxy resin; the electrochemical performance efficiency ηEC is defined as the ratio of the ionic conductivity of the dual-continuous phase solid electrolyte to the ionic conductivity of the liquid electrolyte;
[0024] According to the simulation results, the relationship between porosity, pore size and mechanical performance efficiency, electrochemical performance efficiency and multifunctional efficiency is fitted. Through this relationship, the change law of the mechanical-electrical performance efficiency of the dual-continuous phase solid electrolyte under different ratios can be predicted;
[0025] 2) The rate of change of electrochemical efficiency with strain is defined as the rate of change of the electromechanical properties of epoxy resin-based solid electrolytes, which is used to describe the ability of the electrolyte to maintain its electrochemical properties under an applied load. express,
[0026]
[0027] in, , are the ionic conductivity before and after the load is applied to the electrolyte, , are the strain rates of the electrolyte before and after the load is applied to the electrolyte;
[0028] The parameter data of the force-electric performance change rate of the dual-continuous phase solid electrolyte with different ratios were calculated, and the relationship between the porosity, average pore size and force-electric performance change rate of the dual-continuous phase solid electrolyte was plotted, and the relationship was fitted. Through this relationship, the change law of the force-electric performance of the dual-continuous phase solid electrolyte under different ratios can be predicted.
[0029] Preferably, the mass ratio of the epoxy resin component to the ionic liquid is (1:1) to (8:2), and the number of samples with different ratios is 3 to 4.
[0030] Preferably, in step 2, the structure of the dual-continuous phase solid electrolyte sample is characterized by using SEM, and the porosity and pore size range data are analyzed from the SEM image using Avizo image analysis software;
[0031] Refer to ASTM D4142 standard and use a tensile machine to characterize mechanical properties;
[0032] The bulk impedance of the bicontinuous phase solid electrolyte was tested using an electrochemical workstation, and the ionic conductivity was calculated based on the bulk impedance of the bicontinuous phase solid electrolyte.
[0033] Further preferably, the test parameters of the electrochemical workstation are: AC perturbation voltage 0.1V, frequency range 0.1~106Hz.
[0034] Further preferably, the method for calculating the ionic conductivity according to the bulk impedance of the bicontinuous phase solid electrolyte is as shown in the following formula:
[0035]
[0036] In the formula, is the ionic conductivity, S / cm; is the electrolyte thickness, cm; is the electrolyte bulk impedance, Ω; is the contact area between electrolyte and stainless steel, cm 2 .
[0037] Preferably, the fitting formula obtained by the bicontinuous phase electrolyte force-electrical performance prediction model in step 4 is as follows:
[0038]
[0039] Where p is the porosity and d is the pore size.
[0040] The advantages of the present invention are:
[0041] (1) The research direction of parametric prediction of mechanical and electrical properties of dual-continuous phase solid electrolytes fills the current gap in parametric prediction of the multifunctional properties of dual-continuous phase solid electrolytes and parametric guidance of their forward design and preparation.
[0042] (2) Achieving this research goal by parametric modeling of dual-continuous phase solid electrolytes will accelerate the research and development of directional force-electrical performance dual-continuous phase solid electrolytes and play a certain role in promoting the future engineering applications of dual-continuous phase solid electrolytes.
[0043] (3) As the research on bicontinuous phase solid electrolytes is still in its infancy, the parametric modeling and performance prediction results of bicontinuous phase solid electrolytes can quickly and accurately guide the design and research of bicontinuous phase solid electrolytes and assist in the optimization of the structure and performance parameters of bicontinuous phase solid electrolytes. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 Flowchart for constructing a prediction model for the mechanical and electrical properties of bicontinuous phase electrolytes;
[0045] Figure 2 Porosity-pore size-multifunctional efficiency fitting graph;
[0046] Figure 3 Porosity-pore size-electrochemical performance efficiency fitting graph;
[0047] Figure 4 Porosity-pore size-mechanical properties efficiency fitting graph;
[0048] Figure 5 Porosity-pore size-mechanical / electrical property change rate fitting graph. DETAILED DESCRIPTION
[0049] The technical solution of the invention is further explained below in the form of specific embodiments.
[0050] Example 1 Preparation of dual continuous phase solid electrolyte (EPE) samples:
[0051] The raw materials used in this example are as follows: lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) (≥99.95%, Sigma), ionic liquid 1-ethyl-3-methylimidazolium tetrafluoroborate (IL) (≥99.0%, Sigma), epoxy resin TJ-2000 and curing agent TJ-2060 (Guangzhou Taiji New Material Co., Ltd).
[0052] 1) At room temperature and pressure, first weigh LiTFSI and IL in a mass ratio of 1:10, place them in a container, and stir for 2h-3h until they are evenly mixed.
[0053] 2) Epoxy resin TJ-2000 and curing agent TJ-2060 were weighed out according to the mass ratio of epoxy resin to IL of 1:1, 6:4, 7:3 and 8:2, and the mass ratio of curing agent to epoxy resin was 10:3.
[0054] 3) Add epoxy resin TJ-2000 in different proportions, stir for 1h-2h until uniform, then add curing agent TJ-2060 and continue stirring for 0.5h-1h until uniform, to obtain slurries with different ratios of epoxy resin components and IL.
[0055] 4) Soak the cut glass fiber discs completely in the slurry, and place the prepared slurry in a vacuum oven for degassing and degassing at room temperature. After the degassing and degassing treatment, prepare the button battery sample for the AC impedance (EIS) test, take out the glass fiber cloth with tweezers and place it between the steel sheets. Before putting it in the oven for pressing, use tweezers to squeeze out the excess electrolyte from between the two steel sheets to prevent subsequent steel sheet deviation. Pour the remaining slurry into the compression standard sample mold, lay the button battery sample and the mold flat in a blast drying oven and continue to cure at 60°C for 12 hours. After curing, cool to room temperature and remove the dual-continuous phase solid electrolyte casting from the mold.
[0056] The ratios of epoxy resin component to IL in the dual-continuous phase solid electrolyte casting are 1:1, 6:4, 7:3 and 8:2, which are respectively recorded as EPE50, EPE60, EPE70 and EPE80.
[0057] Example 2 Characterization of the performance of the dual-continuous phase solid electrolyte
[0058] The performance of the dual-continuous phase solid electrolyte sample prepared in Example 1 was tested, and the data was processed to obtain the mechanical and electrochemical performance parameter data required for building the model.
[0059] a. The structures of EPE50, EPE60, EPE70 and EPE80 prepared in step (1) were characterized using a Nova nanoSEM 450 (FEI) scanning electron microscope (SEM):
[0060] First, the liquid phase in the bicontinuous solid electrolyte was removed by ethanol extraction, and then SEM images of the cross-section of each sample were obtained.
[0061] The results show that the microstructures of electrolyte samples with different raw material ratios exhibit different pore sizes and porosities, and when the proportion of ionic liquid increases to a certain value, the morphology of the liquid phase and the solid phase changes from a spherical liquid phase structure to a spherical solid phase structure.
[0062] Then, Avizo software was used to process the SEM images of each sample and analyze the geometric features to extract the porosity, pore size and other geometric features.
[0063] b. Use GOTECH AI-7000SUT tensile testing machine to characterize mechanical properties:
[0064] Referring to the ASTM D4142 standard, the sample compression test was carried out, the dual-continuous phase solid electrolyte slurry was cast into a cylinder with a size of 10mm×25mm, and the sample was subjected to a compression test at a loading rate of 2mm / min.
[0065] According to the analysis of the test results, with the increase of the proportion of liquid phase, the Young's modulus and compressive strength of the samples showed a downward trend. The Young's modulus of EPE80 is 459.7MPa, the Young's modulus of EPE70 is 344.6MPa, the Young's modulus of EPE60 is 236.0MPa, and the Young's modulus of EP50 is 7.9MPa.
[0066] As the proportion of liquid phase in the dual-continuous phase solid electrolyte of EP50 increased, the microstructure changed and the mechanical properties of the sample weakened sharply. Because its solid phase structure was loose, its mechanical properties could not meet the requirements of multifunctional electrolytes, so it was not suitable for application in structure-energy storage integrated devices. Therefore, no further research and testing was carried out on it.
[0067] c. Use an electrochemical workstation to test the electrolyte bulk impedance and calculate the ionic conductivity based on the electrolyte bulk impedance:
[0068] The dual-continuous phase solid electrolyte was made into a stainless steel / electrolyte membrane / stainless steel blocking type battery, and the electrolyte bulk impedance test was performed using an electrochemical workstation. The test parameters were an AC perturbation voltage of 0.1V and a set frequency range of 0.1~106Hz.
[0069] The ionic conductivity (σ) is calculated based on the electrolyte bulk impedance as shown below:
[0070]
[0071] In the formula, is the ionic conductivity, S / cm; is the electrolyte thickness, cm; is the electrolyte bulk impedance, Ω; is the contact area between electrolyte and stainless steel, cm 2 .
[0072] The ionic conductivity of the dual-continuous phase-based solid electrolyte obtained through the above characterization and testing is EPE60, 0.75 mS / cm; EPE70, 0.54 mS / cm; EPE80, 0.34 mS / cm.
[0073] Example 3 Establishment of three-dimensional solid RVE model and simulation analysis method of dual-continuous phase solid electrolyte
[0074] 1) First, set the size of the cubic space, and calculate the number of spheres required for modeling in the cubic space according to the maximum pore size, minimum pore size and porosity data obtained in Example 2. The formula is as follows:
[0075]
[0076] In the formula, is the porosity; is the length of the cubic space region; is the width of the cubic space region; is the height of the cubic space area; is the maximum radius of the pore; is the minimum radius of the pore, and the coefficient 1.1 is used to compensate for the porosity error caused by factors such as pore overlap.
[0077] 2) The center position and radius of the sphere are randomly generated:
[0078] First, the center position of the sphere Using random uniform distribution, which ensures that the entire given space can be filled evenly, the constraints on the seed placement are set as , use the pseudo-random number generator (rand()) to generate the random position coordinates of the seed ,
[0079] Then, using a pseudo-random number generator, within the constraints of the sphere radius R , generates spherical seeds of random size.
[0080] 3) For each sphere, a 3D solid of the sphere was created by rotating the drawn 2D sketch in Abaqus software, and then Boolean operations were applied to subtract these spheres from the cubic matrix to create voids, thus obtaining a 3D solid RVE model of the dual-continuous phase solid electrolyte.
[0081] By comparative observation, the three-dimensional solid RVE model established in this embodiment is similar to the morphology presented by the SEM image of the solid electrolyte, which verifies the rationality of the model structure.
[0082] 4) Simulation and analysis method of performance of dual-continuous phase-based solid electrolyte
[0083] The electrochemical performance of bicontinuous phase-based solid electrolytes depends on the diffusion of ions, so the porous structure of bicontinuous phase-based solid electrolytes directly affects their performance. In other words, the effective ionic conductivity of bicontinuous phase-based solid electrolytes depends on the morphology of the electrolyte microstructure. Especially when bicontinuous phase-based solid electrolytes are used in structure-energy storage integrated devices, the solid electrolyte has both load-bearing and energy storage functions, and when a load is applied, the structural morphology of the electrolyte will change, thereby affecting the diffusion process.
[0084] As a porous heterogeneous phase material, the diffusion of ions in a dual-continuous phase-based solid electrolyte is not exactly the same as the diffusion in a fully solid or liquid electrolyte. The ionic conductivity needs to use an effective value, as shown in the following formula, that is, the diffusion coefficient needs to be considered in the calculation. The calculation process of effective ionic conductivity is as follows:
[0085]
[0086] In the formula, is the liquid phase ionic conductivity in the bicontinuous solid electrolyte, is the effective ionic conductivity of the bicontinuous phase solid electrolyte, S / cm; is the diffusion coefficient, which is calculated as follows:
[0087]
[0088] in, is the porosity, for a two-dimensional cross section, its value is equal to the ratio of the pore area to the total cross section area; is the tortuosity, which is the ratio of the shortest path length between two points to the straight-line distance when transmitting in a porous structure.
[0089] Porosity The calculation formula is as follows:
[0090]
[0091] In the above formula, is the pore area, is the total cross-sectional area of the model;
[0092] In this embodiment, the tortuosity The calculation is performed using the relationship between tortuosity, porosity and pore size fitted in reported studies, as shown in the following formula:
[0093]
[0094] In the formula is a coefficient related to the aperture and is calculated by the following formula:
[0095]
[0096] Where d is the average pore diameter.
[0097] The above principles were used to simulate the mechanical properties and fit the electrochemical properties of the established three-dimensional solid model, and compared with the experimental test results. The EPE simulation performance results of each ratio are: EPE60 modulus is 217.82MPa, ionic conductivity is 0.74mS / cm; EPE70 modulus is 339.63MPa, ionic conductivity is 0.49mS / cm; EPE80 modulus is 456.91MPa, ionic conductivity is 0.32mS / cm. The accuracy of the modeling and simulation analysis methods was verified.
[0098] Example 4 Establishment of a prediction model for the mechanical and electrical properties of a dual-continuous phase electrolyte:
[0099] 1) By analyzing the multifunctionality of the dual-continuous phase-based solid electrolyte, its comprehensive performance and application potential can be evaluated. In order to intuitively evaluate different multifunctionalities, the method proposed by Ashby was used to evaluate the multifunctionality efficiency. The multifunctionality efficiency (ηMF) is defined as follows:
[0100]
[0101] Among them, ηM represents the mechanical performance efficiency, which is defined in the present invention as the ratio of the modulus of the dual-phase solid electrolyte to the modulus of pure epoxy resin; ηEC represents the electrochemical performance efficiency, which is defined in the present invention as the ratio of the ionic conductivity of the dual-phase solid electrolyte to the ionic conductivity of the liquid electrolyte.
[0102] According to the above relevant data, the relationship between porosity, pore size and mechanical performance efficiency, electrochemical performance efficiency and multifunctional efficiency is fitted as follows (the relationship curve is as follows Figure 2~Figure 4 shown):
[0103]
[0104] Where p is the porosity and d is the pore size.
[0105] This relationship can be used to predict the variation of the mechanical-electrical performance efficiency of dual-continuous phase solid electrolytes under different ratios.
[0106] 2) Through simulation analysis of different EPEs under external loads, the effects of different geometric features and mechanical properties on the electromechanical coupling performance of EPE are explored. The rate of change of electrochemical efficiency with strain is defined as the rate of change of electromechanical properties of epoxy resin-based solid electrolytes, which is used to describe the ability of the electrolyte to maintain electrochemical properties under external loads. express,
[0107]
[0108] in, , are the ionic conductivity before and after the load is applied to the electrolyte, , are the strain rates of the electrolyte before and after the load is applied to the electrolyte; their values can be used as an indicator to evaluate the stability of the mechanical-electrical coupling performance of the dual-continuous phase-based solid electrolyte. The mechanical-electrical performance change rate parameter data of EPE with different structures are calculated and plotted as follows: Figure 5 The relationship between the EPE porosity, average pore size and the rate of change of mechanical-electrical properties is plotted, and the relationship is fitted as shown in the following equation.
[0109]
[0110] This relationship can be used to predict the changing law of the mechanical-electrical performance stability of dual-continuous phase solid electrolytes under different ratios.
Claims
1. A method for constructing a prediction model for the mechanical and electrical properties of a dual-continuous phase electrolyte, characterized in that: The specific steps of this method are as follows: Step 1: Prepare several dual-continuous phase solid electrolyte samples with different ratios of epoxy resin components and ionic liquids; Step 2: Perform structural characterization, mechanical property characterization and electrochemical property characterization on the dual-continuous phase solid electrolyte sample prepared in step 1; Step 3: Establishment of three-dimensional solid RVE model and simulation analysis method of dual-continuous phase solid electrolyte 1) First, set the size of the cube space, and calculate the number of spheres required for modeling in the cube space based on the maximum pore size, minimum pore size and porosity data obtained in step 2. The formula is as follows: In the formula, is the porosity; is the length of the cubic space region; is the width of the cubic space area; is the height of the cubic space area; is the maximum radius of the pore; is the minimum radius of the pores, and the coefficient 1.1 is used to compensate for the porosity error caused by factors such as pore overlap; 2) The center position and radius of the sphere are randomly generated: First, the center position of the sphere Using random uniform distribution, which ensures that the entire given space can be filled evenly, the constraints on the seed placement are set as , using a pseudo-random number generator to generate random position coordinates of the seed , Then, using a pseudo-random number generator, within the constraints of the sphere radius R , generate spherical seeds of random size; 3) For each sphere, a 3D solid of the sphere was created by rotating the drawn 2D sketch in Abaqus software, and then Boolean operations were applied to subtract these spheres from the cubic matrix to create voids, thus obtaining a 3D solid RVE model of the dual-continuous phase solid electrolyte; 4) Using the three-dimensional solid RVE model of the bicontinuous phase solid electrolyte with different porosities and pore sizes established in the above steps, the modulus of the bicontinuous phase solid electrolyte and the ionic conductivity of the bicontinuous phase solid electrolyte are obtained by simulation analysis; Step 4: Establishment of a prediction model for the mechanical and electrical properties of a bicontinuous phase electrolyte: 1) The method proposed by Ashby is used to evaluate the multifunctional efficiency, where the multifunctional efficiency ηMF is defined as the sum of the mechanical performance efficiency ηM and the electrochemical performance efficiency ηEC as shown in the following formula: Among them, the mechanical performance efficiency ηM is defined as the ratio of the modulus of the dual-continuous phase solid electrolyte to the modulus of pure epoxy resin; the electrochemical performance efficiency ηEC is defined as the ratio of the ionic conductivity of the dual-continuous phase solid electrolyte to the ionic conductivity of the liquid electrolyte; According to the simulation results, the relationship between porosity, pore size and mechanical performance efficiency, electrochemical performance efficiency and multifunctional efficiency is fitted. Through this relationship, the change law of the mechanical-electrical performance efficiency of the dual-continuous phase solid electrolyte under different ratios can be predicted; 2) The rate of change of electrochemical efficiency with strain is defined as the rate of change of the electromechanical properties of epoxy resin-based solid electrolytes, which is used to describe the ability of the electrolyte to maintain its electrochemical properties under an applied load. express, in, , are the ionic conductivity before and after the load is applied to the electrolyte, , are the strain rates of the electrolyte before and after the load is applied to the electrolyte; The parameter data of the force-electric performance change rate of dual-continuous phase solid electrolytes with different ratios were calculated, and the relationship between EPE porosity, average pore size and force-electric performance change rate was plotted, and the relationship was fitted. Through this relationship, the change law of the force-electric performance of dual-continuous phase solid electrolytes with different ratios can be predicted.
2. The method for constructing a prediction model for the mechanical and electrical properties of a dual-continuous phase electrolyte according to claim 1, characterized in that: The mass ratio of epoxy resin component to ionic liquid is (1:1) to (8:2), and the number of samples with different ratios is 3 to 4.
3. The method for constructing a prediction model for the mechanical and electrical properties of a dual-continuous phase electrolyte according to claim 1, characterized in that: In step 2, the structure of the dual-continuous phase solid electrolyte sample is characterized by using SEM, and the porosity and pore size range data are analyzed from the SEM image using Avizo image analysis software; Refer to ASTM D4142 standard and use a tensile machine to characterize mechanical properties; The bulk impedance of the bicontinuous phase solid electrolyte was tested using an electrochemical workstation, and the ionic conductivity was calculated based on the bulk impedance of the bicontinuous phase solid electrolyte.
4. The method for constructing a prediction model for the mechanical and electrical properties of a dual-continuous phase electrolyte according to claim 3, characterized in that: The test parameters of the electrochemical workstation are: AC perturbation voltage 0.1V, frequency range 0.1~106Hz.
5. The method for constructing a prediction model for the mechanical and electrical properties of a dual-continuous phase electrolyte according to claim 3, characterized in that: The method for calculating ionic conductivity based on the bulk impedance of the bicontinuous phase solid electrolyte is shown in the following formula: In the formula, is the ionic conductivity, S / cm; is the electrolyte thickness, cm; is the electrolyte bulk impedance, Ω; is the contact area between electrolyte and stainless steel, cm 2 .
6. The method for constructing a prediction model for the mechanical and electrical properties of a dual-continuous phase electrolyte according to claim 1, characterized in that: The fitting formula obtained by the prediction model of the mechanical and electrical properties of the dual-continuous phase electrolyte is as follows: Where p is the porosity and d is the pore size.